Analysis of Work Engagement on the Indonesian Broadcasting Commission Staff - Adhitama, Arya Adhitama; Rossanty, Niluh Putu Evvy; Mahardiana, Lina; Wirastuti, Wiri (Borong Newinera Publisher, 2025)
This study aims to analyze work engagement among staff of the Central Sulawesi Broadcasting Commission, a public agency responsible for broadcast oversight. Employing a qualitative case study approach, data were collected through in-depth interviews and participant observations over six months with five purposively selected informants from a total of ten staff members. Data analysis followed an interactive model involving data reduction, presentation, and conclusion drawing. The findings reveal that factors such as simple appreciation, access to modern technology, and participation in special events like elections enhance vigor. Dedication is driven by pride and meaningful work, while absorption is influenced by task urgency, the work environment, and physical condition. The study concludes that both tangible incentives and intangible motivators significantly impact work engagement. It emphasizes the importance of effective workload management and a supportive environment to sustain motivation. Recommendations include improving human resource policies and expanding research scope to include multiple locations and mixed methods for a comprehensive understanding.